The Relationship Between Tattoos and Employee Workplace Deviance. (September 2019) - Tews, Michael J.; Stafford, Kathryn
While those adorned with tattoos have historically belonged to deviant subpopulations, tattoos today are certainly more widespread. With this mainstreaming of tattoos, the question arises whether the deviant stereotype persists and extends to today's workplace. To address this issue, the present study examined the relationships between tattoos and organizational and interpersonal workplace deviance with a sample of 518 individuals employed in restaurant settings. Whether or not an employee was merely tattooed was not related to either form of deviance. However, greater tattoo number was associated with greater organizational deviance. In addition, the results suggest that being adorned with "darker" tattoos was related to both types of deviance, although the effect sizes were not large. The significant findings held even after controlling for the employees' agreeableness and conscientiousness.